Scouting for Citrus Greening: Scouting Today to Protect Future Profits: CH201/CH201, 8/2008 - Yates, Jamie D.; Futch, Steve H.; Spann, Tim M. (EDIS, 2009)
CH201, a 2-page trifold brochure by J.D. Yates, S.H. Futch, and T.M. Spann, highlights the purpose of scouting, frequency, methods, grove conditions, tagging suspect trees, scout responsibilities, safety concerns, diagnostics, and what to scout for. Includes contact information for UF/IFAS Extension citrus experts. Published by the UF Department of Horticultural Sciences, August 2008. *J.D. Yates' name has changed to J.D. Burrow. CH201/CH201: Scouting for Huanglongbing (HLB; Citrus Greening) (ufl.edu)